Vision and Leadership: The Nature, Role and Development - Marina; Rasyimah; Dewi Kumala Sari (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
Every leader has their leadership style. Visionary leadership is a style that emphasizes the need for a clear vision for the future of an organization. Vision affects how the people within the organization perform and how the organization adapts to forthcoming changes. The organization's style, culture and purpose affect how a leader forms a vision. This paper aims to analyze visionary leadership's nature, role and development. A case of a leadership situation shows that a leader with a strong vision would create strategic choices and judgements for the better growth of the organization.